2021
DOI: 10.3390/ijms222312779
|View full text |Cite
|
Sign up to set email alerts
|

Synaptamide Improves Cognitive Functions and Neuronal Plasticity in Neuropathic Pain

Abstract: Neuropathic pain arises from damage or dysfunction of the peripheral or central nervous system and manifests itself in a wide variety of sensory symptoms and cognitive disorders. Many studies demonstrate the role of neuropathic pain-induced neuroinflammation in behavioral disorders. For effective neuropathic pain treatment, an integrative approach is required, which simultaneously affects several links of pathogenesis. One promising candidate for this role is synaptamide (N-docosahexaenoylethanolamine), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
(97 reference statements)
2
9
0
Order By: Relevance
“…Additionally, we observed an increase in the levels of TNF-α and IL-1β and a decrease in the levels of IL-4 and IL-10 in the hippocampus. These results indicate that neuropathic pain induces neuroin ammation in the hippocampus, which is consistent with previous research [40] , [41] , [6] and supports the neuromediator theory.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we observed an increase in the levels of TNF-α and IL-1β and a decrease in the levels of IL-4 and IL-10 in the hippocampus. These results indicate that neuropathic pain induces neuroin ammation in the hippocampus, which is consistent with previous research [40] , [41] , [6] and supports the neuromediator theory.…”
Section: Discussionsupporting
confidence: 93%
“…41,42 Because of these biological functions, synaptamide play a role in improving cognitive function and neuronal plasticity in neuropathic pain. 43 What's more, Park et al demonstrated the immunomodulatory effects of ADGRF1 in the brain and in the periphery, and jointly promoted the anti-neuroin ammatory effects of synaptamide in systemic in ammatory conditions. These results suggest that ADGRF1 mediated inhibition of innate immune cell activation may be a novel therapeutic strategy for controlling brain and/or peripheral in ammation and related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found that curcumin can alleviate CCI-induced neuropathic pain in rats by remarkably increasing the number of newborn neurons and improving hippocampal neurogenesis and synaptic plasticity ( Du et al, 2021 ). Synaptoamine treatment ameliorated neuropathic pain in mice by reversing decreased dendritic density, worsening hippocampal neurogenesis, and long-term potentiation damage in ca1 pyramidal neurons ( Tyrtyshnaia et al, 2021 ). In this study, the HT22 hippocampal neuron cell line was selected for exploration, and it was found that baicalein and wogonin could promote the occurrence, angiogenesis and proliferation of HT22 cells to relieve pain.…”
Section: Discussionmentioning
confidence: 99%